(untitled) (Scientific journal of the Fergana State University, 2026)
A strain of Streptomyces albidoflavus isolated from soil can be transmitted to the bacteria Klebsiella pneumoniae, Proteus mirabilis, Staphylococcus aureus (MRSA),Staphylococcus aureus (MSSA), E. coli in order to detect secondary metabolites outside the esophagus, the enzymatic activity of a liquid and an extract containing pathogenic microorganisms. It is known that the enzymatic broth has antibacterial activity only against Staphylococcus aureus (MRSA) at D = 25 mm, and the extract composition is active against all pathogenic bacteria at d = 20-32 mm, forming clear transparent zones for penetration.